Design and analysis of connections in steel structures : fundamentals and examples - Boracchini, Alfredo (Ernst & Sohn, a Wiley Brand, 2018)
This book introduces all the aspects needed for the safe and economic design and analysis of connections using bolted joints in steel structures. This is not treated according to any specific standard but making comparison among the different norms and methodologies used in the engineering practice, e.g. Eurocode, AISC, DIN, BS. Several examples are solved and illustrated in detail, giving the reader all the tools necessary to tackle also complex connection design problems.
Keywords: Bridges -- Design and construction.; Iron and steel bridges -- Design and construction.; elektronické knihy; electronic books